Customer behaviour toward social networking advertising - Phang, Chia Lee (Universiti Malaysia Sarawak, (UNIMAS), 2013)
Social networking has increasingly penetrating in our social lives where people keep in contact with their friend or family through this media and even on a daily basis. social networking has become new medium for advertiser for marketing purpose. The social network sites allow its users to share a process of discussing, experiences and opinions of people from all over the world with high efficiency. This study aimed to investigate factors and relationship that influence customer purchase intention in the context of their use of social networking advertising.